The problem of depending on fossil fuels in the energy policies of the european union: A strategic analysis in the eastern mediterranean region - Alhan, Mehmet Ali (Springer Science and Business Media Deutschland GmbH, 2022)
The Eastern Mediterranean geographical area consists of an area surrounded by Europe in the North, Asia in the East, the Middle East in the Southeast, and Africa in the South. The Republic of Turkey is the country with the longest coastline in this area. Recently, the discovery of increasing hydrocarbon reserves in this geography has whetted the appetite of the European Union (EU) countries that cannot meet their energy needs. Federal Germany, which has the largest industrial capacity among the European Union countries with energy dependence on the Russian Federation, had an urgent and important need for an alternative, reliable, and clean energy supply, especially during the Russia-Ukraine crisis. In this study, the European Union’s process of closing nuclear and hydroelectric power plants for alternative, reliable, and clean energy and the depletion of fossil fuels will be discussed. It will be argued that energy domination has a very strategic meaning. In the process of liberation from fossil fuel, the search for gas hydrate and the political, economic, and cultural relations of the Republic of Turkey with Europe will be discussed.
Keywords: Carbon Emission; Eastern Mediterranean; Energy Dependency; Energy Diplomacy; Gas Hydrate